Improvement of actions on emergency situations at transportation of dangerous freights by rail transport - Kosenko, Ye. Ya.; Kukhlivs’kyi, S. V.; Bondarenko, B. M.; Podzigun, I. I. (Science and Transport Progress, 2013)
Purpose. Improvement of actions of emergency-and-rescue services during elimination of emergency aftermaths on railway. The extraordinary situations of anthropogenic character on railway are determined by the features of striking factors and are divided into accidents (catastrophes), accompanied by exhausts (blow-outs, spills) of hazardous substances, fires, explosions, failures on engineering networks and systems of life-support, by destruction of buildings and structures, by accidents of transport vehicles, etc. At present, there is a problem of co-operation planning of troops and facilities, ministries and departments, which are ordered for eliminating the aftermaths of extraordinary situations, particularly at transporting dangerous freights by rail. Methodology. During the research the method of search optimization of existing systems improvement of analysis and forecast of extraordinary situations as well as the supervision and hour-by-hour registration of rescue services actions during trainings and in the real conditions of aftermaths eliminating of extraordinary situations were used. Findings. The problems to solve are notifying the population on the threat of extraordinary situations arising, informing in time about a current situation, maintaining emergency-and-rescue services in readiness to functioning in extraordinary situations, organizing the life-support of population in conditions of accidents, catastrophes, or a natural calamity. Originality. The features of civil defense organization at dangerous freights transportation are explored; the order of co-operation of emergency-and-rescue services during the elimination of emergency aftermaths of anthropogenic origin on railway is developed. It is resulted in creating the conditions of relative diminishment of losses and expenditures because of transport accidents, catastrophes, explosions, conflagrations and natural calamities. Practical value. It is necessary to plan emergency-and-rescue and other exigent works in the areas of extraordinary situations on railway at transportation of dangerous freights in the case of their occurrence with the simultaneous bringing the troops and facilities of ministries and departments, inter-sectoral consortia, corporations, business concerns, associations etc., which appear in the area of extraordinary situation with the preliminary determination of their subordination to implement these measures.